Juridical Review of Chemical Castration Action In The Perspective of Criminal Law And Human Rights - Aulya Dwisudarini; Muridah Isnawati (Faculty of Law, Merdeka University Surabaya, 2021)
Children are a gift from God Almighty must be maintained for their survival because children are the future and next generation of the nation. A state commits protecting the children's rights and ensuring children's welfare by issuing several laws and regulations accommodating all children's needs and rights. However, this have not reduce the case numbers of sexual violence against children yet, therefore, the government issued a new regulation, namely Law Number 17 of 2016 which regulates new sanctions for perpetrators of sexual violence and the addition of chemical castration. The purpose of this research is to find out the juridical review of chemical castration in the perspective of criminal law and human rights. The research method used in this research is normative jurisdiction using a law approach. The results of the study found that chemical castration is appropriate for perpetrators of sexual violence against children, because sexual violence against children is a serious, cruel crime. Chemical castration does not violate human rights because it aims to normalize the hormones of pedophiles and the rehabilitation carried out by medical experts is aimed at enabling pedophiles to be normal human beings physically and mentally.